Playful educational strategies for assessing students' perspectives on drug addiction in a public school environment - Mariana Balhego Rocha; Maricana Demarchi; Thais Pasqualli (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2026)
Adolescence is a period of developmental transition in which initial exposure to substances often occurs. In this context, schools and teachers play a crucial role in preventive education. This study aimed to strengthen cognitive dimensions and attitudes regarding drug prevention among eighth-year students in a public school in Uruguaiana through creative educational strategies, including fanzines, theatrical performances, and musical compositions. These activities were developed under the guidance of professors and graduate students from the Pharmacy and Education programs. Students produced a fanzine with informational texts and warnings about substance-related harms; the play staged dialogues between characters and their conscience to portray real-life conflicts and outcomes; a rap concluded the performance, critically addressing social and existential dimensions of substance use. A retrospective pretest–posttest questionnaire was administered to participating student actors (n = 23) to assess perceptions of impact and engagement. Overall, 94% reported that the play had a positive impact on the audience. Students described feeling challenged and valued while conveying messages to peers, highlighting their engagement in acting, scriptwriting, rehearsals, and performance. They also reported gains in oral expression, spatial/body awareness, and in integrating artistic expression with critical social themes. Findings suggest that arts-based, school-embedded activities can promote student engagement and personal growth while enhancing understanding of substance-related issues and the importance of preventive education.